Enrichment of Murine CD68(+)CCR2(+) and CD68(+)CD206(+) Lung Macrophages in Acute Pancreatitis-Associated Acute Lung Injury - Akbarshahi, Hamid (Public Library of Science, 2012)
Acute lung injury (ALI) is an important cause of mortality in critically ill patients. Acute pancreatitis (AP) is one of the risk factors for developing this syndrome. Among the inflammatory cells, macrophages have a key role in determining the severity of the acute lung injury. In the lungs, macrophages constitute a heterogeneous cell population distributed in different compartments. Changes in not only the macrophage count, but also in their phenotype have been seen during the course of lung injury. A murine ductal ligation model of acute pancreatitis showed substantial morphological changes in the pancreas and lungs. Immunohistochemistry showed neutrophil recruitment into both organs after 9 hours and later on. F4/80(+) cells in the pancreas increased in the ligated animals, though there was not a significant difference in their number in the lungs as compared to sham operated animals. Flow cytometry analysis of lung macrophages demonstrated an enrichment of F4/80(−) CD68(+)CCR2(+) and F4/80(−) CD68(+)CD206(+) lung macrophages in ligated animals (AP) as compared to the sham operated group. The level of interleukin-6 in plasma increased 3 hours after ligation compared to the sham operated group, as a first indicator of a systemic inflammatory response. This study suggests a role for F4/80(−) CD68(+) macrophages in the pathogenesis of acute lung injury in acute pancreatitis. Studying lung macrophages for different phenotypic markers, their polarization, activation and recruitment, in the context of acute lung injury, is a novel area to potentially identify interventions which may improve the outcome of acute lung injury.